Изменения
Перейти к:
навигация
,
поиск
← Предыдущая правка
Следующая правка →
Формула полной вероятности
57 байт добавлено
,
02:31, 15 января 2011
Нет описания правки
<tex> {P}( AB_i) = {P} (B_i) {P} (A \mid B_i) </tex>
Окончательно получаем:
<tex>{P}(A) = \sum\limits_{i=1}^{n} {P}( A \mid B_i) {P}(B_i)</tex>
==Замечание==
Анонимный участник
192.168.0.2
Навигация
Персональные инструменты
Создать учётную запись
Войти
Пространства имён
Статья
Обсуждение
Варианты
Просмотры
Читать
Просмотр вики-текста
История
Ещё
Поиск
Навигация
Заглавная страница
Свежие правки
Случайная статья
Справка
Инструменты
Спецстраницы
Версия для печати